Comparison of Left Radial Versus Femoral Approaches for Coronary Procedures in Patients with Previous Coronary Artery Bypass Grafts (Anwer Khan Modern Medical College Journal, 2019)
Aims: Radial approach is gaining the momentum as a default technique for coronary procedures. Limited trails are available for post coronary artery bypass graft (CABG) patients to compare the merits of femoral & radial access.Methods: It is a single-center study conducted in between January, 2013 to December, 2015. During this study period, post CABG patients were blindly assigned to its five high volume operators. Coronary angiography & intervention procedures were performed by left radial or femoral approach as per assigned operator's choice. Contrast volume was the primary endpoint whereas the procedure & fluoroscopy time, procedural success, access site major bleeding, pre discharge major adverse cardiac event (MACE) were the secondary endpoint both for coronary angiogram (CAG) & percutaneous coronary intervention (PCI).Results: Total 380 post CABG patients were included in this study period. Radial access (n=155) was lower than femoral access (n=225). Compared with femoral access, diagnostic CAG required relatively lower contrast volume though statistically not significant via radial access (70±34 vs. 72±40 ml, p=0.267). Procedure time (25.2±10.7 vs. 26.9±6.8 min, p=0.735), fluoroscopy time (10.7±5.5 vs. 9.5±4.7 min, p=0.424) were almost similar in both access for CAG. Other secondary clinical endpoints were similar among both groups. Interestingly, adhoc PCI was more frequent in radial group (n=54 out of 155, 34.8%) than in femoral group (n=44 out of 225, 19.6%) with p=0.01. Contrast volume in between two groups was pretty similar with p=0.226. The incidence of other secondary endpoints was also not statistically significant.Conclusion: Coronary angiography for post CABG patients through left radial approach seems to be effective, non-inferior in terms of contrast volume, procedure & fluoroscopy time & other clinical end points comparing to femoral access.Anwer Khan Modern Medical College Journal Vol. 10, No. 1: Jan 2019, P 11-16